Effects of Crossbreeding and Concentrates Feeding on Growth Rates of Goat Kids Reared under Highlands Conditions - Maria Sauer; Ioan Pădeanu; Neculai Dragomir; Walter-Ioan Sauer; Sorin-Octavian Voia; Dinu Gavojdian (Scientific Papers Animal Science and Biotechnologies, 2023)
Aim of the current research was to evaluate the effects that crossbreeding and concentrates feeding have on growth performance of goat kids managed under pasture conditions of the Romanian highlands. Experiments were carried out at the Research and Development Station for Sheep and Goats from Caransebes, in south-western Romania. The growth performances of two kids genotypes were studied, Carpatina purebreds and F1 Boer x Carpatina crossbred kids, respectively. Under two experimental variants, with no concentrates allowance and with 300 g/day concentrates supplementation of the ration, respectively. Carpatina purebred kids had an average daily gain of 100.7±0.03 g/day when managed exclusively on pastures (control group), while the group fed with concentrates registered growth rates of 124.4±0.02 g/day (p≤0.05). The F1 Boer x Carpatina crossbreeds had growth rates of 145.2±0.02 g/day when kept exclusively on pasture, while the group fed with additional concentrates registered growth rates of 211.9±0.04 g/day (p≤0.01). Genotype of the kids affected significantly (p≤0.001) the growth rates, in both experimental variants. It was concluded that both crossbreeding and, to a leaser extent concentrates feeding of kids, are influencing the growth rates of fattening kids managed under highlands conditions of Romania.